Studi Komparatif Kemampuan Berpikir Kritis Siswa pada Penerapan PBL Berbasis dan Tidak Berbasis Video Animasi: Penelitian - Widnyandari, Ni Ketut; Astawa, Ida Bagus Made; Sriartha, I Putu (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
This study aims to analyze the differences in students' critical thinking skills between classes implementing the Problem-Based Learning (PBL) model based on Canva animated videos and classes without animated videos in geography learning. The study used a comparative quantitative approach and was conducted at SMA Negeri 1 Kubutambahan with a population of 166 grade X students from five classes. The sample was determined using a purposive random sampling technique. Data were collected through observations of the implementation of the learning model and essay tests, then analyzed using descriptive analysis and different tests (t-tests). The results showed a significant difference in students' critical thinking skills, where the use of Canva animated videos in the PBL model provided a greater increase compared to the class without animated videos, although an increase in critical thinking skills also occurred in the non-experimental class.